Acute Effect of a Dried Ethanol-Water Extract of Garlic on the Microhaemovascular System of the Skin - Wohlrab, Johannes; Wohlrab, David; Marsch, Wolfgang Ch (Arzneimittelforschung, 2000)
In the present study, the acute vasoactive effect of a dried hydrophilic extract of garlic with 600 mg active substance (Alliosan®) was investigated in 10 healthy volunteers. Laser-Doppler fluxmetry, video capillary microscopy and transcutaneous partial pressure of oxygen measurements were used for the objective assessment of functional and morphological parameters. An increase in perfusion could be demonstrated by these means. This was based on an increase in erythrocyte flow velocity of up to 2 h duration, which was mainly due to vasodilation in both arterial and venous vessels. A change in transcutaneous partial pressure of oxygen or an influence on sympathetically-mediated vasomotor reflexes could not be demonstrated. Furthermore, there was no evidence of an influence on reactive hyperaemia after controlled hyperthermia. The test substance was shown to increase the cutaneous microperfusion.
Keywords: Alliosan®; Garlic, drug extract, effect on cutaneous microcirculation, vasodilation